The Politicization of Radicalism Issues and Its Impact on Social Harmony in Multicultural Societies: An Analysis of Interfaith Student Perspectives in Kendari - Taufani Taufani; Zainal; Hidayah Rahman; Tita Juwita Nur (Journal of Law, Social Science and Management, 2026)
Background: Radicalism has become one of the most contested sociopolitical issues in Indonesia, a nation characterized by profound religious, ethnic, and cultural diversity. Objectives: This qualitative study investigates how radicalism discourse is politicized in multicultural campus environments and the consequences of such politicization for interfaith social harmony in Kendari, Southeast Sulawesi. Method: Drawing on in-depth interviews with sixteen student informants representing eight campus-based religious and sociopolitical organizations — KAMMI, HMI Dipo, HMI MPO, IMM, PMKRI, Hindu Student Organization, GMKI, and Gema Pembebasan — the study finds that radicalism narratives are frequently weaponized as electoral instruments to discredit political opponents, thereby reinforcing identity-based polarization. Results: Informants consistently observed that the misuse of the "radical" label generates stigma against specific religious or cultural identities, erodes social trust (social trust), promotes defensive exclusivism among previously open communities, and suppresses freedom of cultural and religious expression in public spaces. Conclusion: The study argues that addressing these dynamics requires inclusive political leadership, culturally grounded deradicalization strategies rooted in local wisdom (kearifan lokal), and a reform of multicultural education to move beyond theoretical tolerance toward authentic, practice-based intercultural engagement.